On Contra $\mathcal{I}_g$-continuity in Ideal Topological Spaces (Journal of Informatics and Mathematical Sciences, 2011)
In this paper, $\mathcal{I}_g$-closed sets and $\mathcal{I}_g$-open sets are used to define and investigate a new class of functions called contra $\mathcal{I}_g$-continuous functions in ideal topological spaces. We discuss the relationships with some other related functions.
Keywords: $\mathcal{I}_{g}$-closed sets; $\mathcal{I}_{g}$-continuity; contra $\mathcal{I}_{g}$-continuity and contra $*$-continuity